2013
DOI: 10.1371/journal.pone.0077798
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Five Human Lactoferrin Transgenic Cloned Goats Using Fibroblast Cells and Their Methylation Status of Putative Differential Methylation Regions of IGF2R and H19 Imprinted Genes

Abstract: BackgroundSomatic cell nuclear transfer (SCNT) is a promising technique to produce transgenic cloned mammalian, including transgenic goats which may produce Human Lactoferrin (hLF). However, success percentage of SCNT is low, because of gestational and neonatal failure of transgenic embryos. According to the studies on cattle and mice, DNA methylation of some imprinted genes, which plays a vital role in the reprogramming of embryo in NT maybe an underlying mechanism.Methodology/Principal FindingsFibroblast cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…H19 expression was decreased, which is in agreement with findings in cloned piglets (Wei et al, 2010). Published studies have revealed that H19 expression was unchanged (Inoue et al, 2002) and that methylation of the H19 DMR resembles that of normal controls in SCNT cloned mice (Han et al, 2008;Shen et al, 2012;Meng et al, 2013). The H19 DMR regulates expression of both H19 and IGF2 (Le et al, 2013); thus, hypermethylation of the H19 DMR would repress H19 expression.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…H19 expression was decreased, which is in agreement with findings in cloned piglets (Wei et al, 2010). Published studies have revealed that H19 expression was unchanged (Inoue et al, 2002) and that methylation of the H19 DMR resembles that of normal controls in SCNT cloned mice (Han et al, 2008;Shen et al, 2012;Meng et al, 2013). The H19 DMR regulates expression of both H19 and IGF2 (Le et al, 2013); thus, hypermethylation of the H19 DMR would repress H19 expression.…”
Section: Discussionsupporting
confidence: 87%
“…The H19 DMR regulates expression of both H19 and IGF2 (Le et al, 2013); thus, hypermethylation of the H19 DMR would repress H19 expression. Published studies have revealed that H19 expression was unchanged (Inoue et al, 2002) and that methylation of the H19 DMR resembles that of normal controls in SCNT cloned mice (Han et al, 2008;Shen et al, 2012;Meng et al, 2013). However, in fetuses of ESC cloned mice, H19 was decreased (Humpherys et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lactoferrin is an 80-kDa protein from the transferrin family that is responsible for binding, transport and metabolism of iron ions (Iyer & Lonnerdal 1993). Lactoferrin has been transferred and expressed in several animal species (Chen et al 2008;Meng et al 2013;Cooper et al 2015). Transfer of human lactoferrin driven by the carp b-actin promoter to grass carp (Ctenopharyngodon idellus) delayed the onset of clinical signs in grass carp fry injected with grass carp haemorrhagic virus (GCHV) (Zhong et al 2002).…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%